Exploration of an effective training system for diagnosis of superficial esophageal squamous cell carcinoma with magnifying narrow‐band imaging: Prospective research. Issue 5 (27th November 2020) - Fan, Mengke; Qi, Cuihua; Wang, Weijun; Shi, Huiying; Han, Chaoqun; Hou, Xiaohua; Lin, Rong
Abstract : Background and aims: The aim was to explore an effective training system for diagnosis of superficial esophageal squamous cell carcinoma (SESCC) and its staging with magnifying narrow‐band imaging (M‐NBI). Patients and methods: Fifteen endoscopists with no or less M‐NBI experience participated in this training, which consisted of four stages and five teaching methods (M‐NBI classification criterion, case analysis, hands‐on operation, error correction and SESCC pathological knowledge). M‐NBI images were evaluated and diagnostic accuracy was analyzed. Results: After training, the accuracy of distinguishing neoplastic esophageal from non‐neoplastic (0.58 ± 0.16 vs. 0.95 ± 0.05, P  = 0.000) and diagnosing SESCC staging (0.25 ± 0.26 vs. 0.89 ± 0.08, P  = 0.000) with M‐NBI were significantly increased. Participants with no M‐NBI experience achieve equivalent diagnostic accuracy with less experienced trainees after the training (0.91 ± 0.08 vs. 0.92 ± 0.04, P  = 0.816). Besides, diagnosis of MM (muscularis mucosa)/SM1 (submucosal) staging tumors (Stage I, 0.47 ± 0.15; Stage II–III–IV, 0.76 ± 0.12) with M‐NBI was difficult for trainees and should be the focus of this training. Every teaching method could improve the diagnostic accuracy for esophageal lesions, especially for case analysis (from 0.59 ± 0.10 to 0.85 ± 0.08, P  = 0.000). In addition, the average operation score for trainees was significantly increased after hands‐on teaching (60.40 ± 11.11 vs. 91.80 ± 4.28, P  = 0.0001). Conclusions: For novices, this training system showed efficient performance for diagnosing SESCC staging with M‐NBI. Diagnosing MM/SM1 staging SESCC was difficult for beginners, and should be the focus of training.